Pengaruh Penggunaan Game Edukasi Berbasis Wordwall Dalam Pembelajaran Matematika Terhadap Motivasi Belajar Siswa SMP Plus Tahdzibun Nasyiin - Diana Putri; Riska Binti Fatatin Azizah; Moh. Syadidul Itqan (Relevancia: Jurnal Pendidikan dan Pembelajaran, 2024)
The purpose of this study was to determine the effect of using Wordwall-based educational game media in mathematics learning on students' learning motivation. The method used was a descriptive quantitative approach through a learning motivation questionnaire. The respondents involved were 35 eighth-grade students of SMP Plus Tahdzibun Nasyiin. The results of the data analysis resulted in the conclusion that almost all students were able to accept this learning method. This is indicated by almost all students having high to very high learning motivation. This conclusion indicates that the use of Wordwall media has a positive impact on increasing student learning motivation.